Exploring International Students' Food Choices Using Photovoice Techniques - Corcoran, Nova (Journal of International Students, 2018)
This study aimed to explore international student food choices in a semi-rural setting using participatory photovoice techniques. Eighteen international students took photographs over 7–10 days of a typical food week and then attended a workshop where they completed three photography display and captioning tasks. Ten themes emerged linked to the food choices made by international students. These themes were aligned to a social determinants of health model and findings are discussed in the context of improving international students’ food experiences through focusing on individual lifestyles, social networks and living and learning environments.